Acridine Orange: A Review of Novel Applications for Surgical Cancer Imaging and Therapy - Byvaltsev, Vadim A.; Bardonova, Liudmila A.; Onaka, Naomi R.; Polkin, Roman A.; Ochkal, Sergey V.; Shepelev, Valerij V.; Aliyev, Marat A.; Potapov, Alexander A. (Frontiers in Oncology, 2019)
Introduction Acridine orange (AO) was first extracted from coal tar in the late 19th century and was used as a fluorescent dye. In this paper, we review emergent research about novel applications of AO for fluorescence surgery and cancer therapy. Materials and methods We performed a systematic search in the MEDLINE, PubMed, Cochrane library, Google Scholar, Embase, Web of Science and Scopus database using combinations of the term “acridine orange” with the following: “surgical oncology”, “neuropathology” , “microsurgery”, “intraoperative fluorescence”, “confocal microscopy”, “pathology”, “endomicroscopy”, “guidance”, “fluorescence guidance”, “oncology”, “surgery”, “neurooncology” and “photodynamic therapy”. Peer-reviewed articles published in English were included in this review. We have also scanned references for relevant articles. Results. We have reviewed studies on the various application of AO in microscopy, endomicroscopy, intraoperative fluorescence guidance, photodynamic therapy, sonodynamic therapy, radiodynamic therapy. Conclusion Although the number of studies on the clinical use of AO is limited, the pilot studies demonstrated safety and feasibility of its application as an intraoperative fluorescent dye and as a novel photo- and radio-sensitizator. Further clinical studies are necessary to more definitively assess the clinical benefit AO-based fluorescence guidance and therapy for sarcomas and establish feasibility of this new approach for the treatment of other tumor types.